Relief sculpture and its role in enriching field sculptural work surfaces - gamal yahya mohamed sedky (Journal of Architecture, Art & Humanistic Science, 2023)
Research SummaryRelief sculpture has an important role in enriching the surfaces of field sculptural work, due to its multipurpose and aesthetic and functional dimensions that make it spread aesthetic taste by creating artistic methods that enrich the surfaces of field sculptural work through the art of relief sculpture that works on assembling and mixing plastic elements within the design, various movement rhythms and rhythms occur, which in turn serve the expressive aspectThe researcher used a variety of movements of people who seem to extend their hands as an expression of the ascension, the expressive role of these people is a representation of the souls of the martyrs whom God Almighty has spoken to us to demonstrate the status that He has promised them in the hereafter, and these people are the main focus of the subject of the work carried out and specially designed in their honor. The researcher made use of the ancient Egyptian method in his approach to treat field sculptural work surfaces with hieroglyphic inscriptions and symbols.The art of relief sculpture is considered the first means of expressing the most important aspects of social life, religious beliefs and historical heroism of what the different spaces and surfaces allow. He benefited from the characteristics of bas-relief and bas-relief in enriching the surface values of his sculptures and imparting them sensory and visual aesthetic values through the method of recessed sculpture and what he makes on the surfaces through the lights and shadows that fall on the surface so that they have a beautiful impact in the soul, and that sometimes the Egyptian artist was not satisfied with drilling only. We sometimes see those hieroglyphic shapes and letters in a different color from the ground, so they stand out minute in the contour of the shapes or vary in the texture to make the work surface polished and the shapes rough.